Adapted Active Appearance Models. (13th December 2009) - Séguier Séguier, Renaud Renaud; Le Gallou Le Gallou, Sylvain Sylvain; Breton Breton, Gaspard Gaspard; Garcia Garcia, Christophe Christophe
Abstract : Active Appearance Models (AAMs) are able to align efficiently known faces under duress, when face pose and illumination are controlled. We propose Adapted Active Appearance Models to align unknown faces in unknown poses and illuminations. Our proposal is based on the one hand on a specific transformation of the active model texture in an oriented map, which changes the AAM normalization process; on the other hand on the research made in a set of different precomputed models related to the most adapted AAM for an unknown face. Tests on public and private databases show the interest of our approach. It becomes possible to align unknown faces in real-time situations, in which light and pose are not controlled.